Radial Compressive Mechanical Behavior of 2D Plain‐Woven SiCf/SiC Cladding Tube. Issue 2 (25th November 2018) - He, Zongbei; Zhang, Ruiqian; Fu, Daogui; Chen, Zhaoke; Li, Ming; Qiu, Shaoyu
Abstract : In this paper, the 2D plain‐woven SiCf /SiC cladding tube is fabricated by CVI process and its radial compressive mechanical behavior is studied. Under the action of radial compressive load, the hoop stress and interlaminar shear stress are non‐negligible for the SiCf /SiC cladding tube, and the main failure modes consist of bending fracture and interlamination delamination which are resulted from the hoop stress and the interlaminar shear stress, respectively. Based on the ISO 2739–2012 standard, the radial crushing strength can be determined for the tube with failure mode of bending fracture, and for the SiCf /SiC cladding tubes investigated in this paper, the radial crushing strength is ranged from 330 to 361 MPa. But, when the delamination failure is triggered during the test, the crushing strength is failed to be acquired. Moreover, for the bending fracture case, the relationship between the radial crushing strength and the hoop tensile strength can be built by two methods. Abstract : The goal of this paper is to understand the stress distributions, failure modes as well as the radial crushing strength of SiCf /SiC tube under radial compressive load. Under the action of radial compressive load, both bending fracture and delamination can be triggered which result from the hoop stress and interlaminar shear stress, respectively.